2020
DOI: 10.1101/2020.01.17.907618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complement C5a impairs phagosomal maturation in the neutrophil through phosphoproteomic remodelling

Abstract: Critical illness is accompanied by the release of large amounts of the anaphylotoxin, C5a. C5a suppresses antimicrobial functions of neutrophils which is associated with adverse outcomes. The signalling pathways that mediate C5a-induced neutrophil dysfunction are incompletely understood. Healthy donor neutrophils exposed to purified C5a demonstrated a prolonged defect (7 hours) in phagocytosis of Staphylococcus aureus. Phosphoproteomic profiling of 2712 phosphoproteins identified persistent C5a signalling and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Patients with suspected VAP, including those with ARDS, demonstrated impaired phagocytic function of alveolar neutrophils, which interestingly appeared to be mediated by different mediators than those driving dysfunction in the peripheral blood [ 9 ]. While we have a growing understanding of the mediators driving dysfunction, and the intracellular mechanisms which drive them [ 14 ], we do not as yet have proven therapies although there are multiple potential agents [ 7 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Patients with suspected VAP, including those with ARDS, demonstrated impaired phagocytic function of alveolar neutrophils, which interestingly appeared to be mediated by different mediators than those driving dysfunction in the peripheral blood [ 9 ]. While we have a growing understanding of the mediators driving dysfunction, and the intracellular mechanisms which drive them [ 14 ], we do not as yet have proven therapies although there are multiple potential agents [ 7 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…This effect is independent of CD88. In the current study it seems reasonable to assume that co-infection with linezolid must influence this critical C5a signalling period and its effect is independent of cell surface CD88, but dependent on effects produced intracellularly on pHi or maturation of the phagosome 20 , 25 .…”
Section: Discussionmentioning
confidence: 76%
“…Thus, ligation of C5aR1 (CD88) by C5a, activates its inherent G-protein activity resulting in phosphoinositide 3-kinase delta (PI3Kδ) activation inhibiting activation of the small GTPase RhoA, actin polymerisation and phagocytosis 13 . At the time of writing Wood and co-workers confirmed that C5a induced decreases in the phagocytosis of S. aureus are associated with impaired phagosomal maturation by phosphoproteomic remodelling through selective impairment of phagosomal protein phosphorylation, including endosomal marker ZFYVE16 and V-ATPase protein channel component ATPV1G1 25 . In addition, Denk and co-workers proposed that C5aR1 ligation also leads to selective activation of the Na + /H + exchanger causing increased intracellular alkalinisation (pHi), increased glycolytic flux, glucose uptake and lactate and proton excretion 20 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations